Relationship between psychological contract and organisational commitment at Felda Holdings Berhad - Nooralias Fikri bin Abdul Samad (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2009)
Psychological contract is essentially an expansion of the concept social contract into the psychological domain. Whereas social contract refers to unwritten set of rights and obligations that determine the nature of relationship between the state and its citizens, psychological contract covers more of the relationship between employees and organisations. Though it remains unwritten, psychological contract is a powerful determiner of behaviour in organisations. Example of such organisational behaviour being influenced by psychological contract is one’s commitment to the organisation. The aim of this research is to examine the relationship between psychological contract organisational commitment. For this purpose, a sample of 126 respondents from Felda Holdings Berhad, a Malaysian government-linked-company (GLC) was given the Psychological Contract Scale (PCS) and the Affective, Continuance and Normative Commitment Scales (ACN-CS) for them to complete. Both of these scales have been translated into Bahasa Malaysia using the committee approach which involves the researcher and two lecturers from the Department of Psycholgy, International Islamic University Malaysia. Completed questionnaires were then analysed using Pearson Product Moment Correlation Coefficient to determine whether there was a significant relationship between components of psychological contract (transactional and relational) and components of organisational commitment (affective, continuance and normative). Results from this research showed that transactional contract was positively related to continuance commitment but it was vice versa with both affective and normative commitments. All of these relationships were significant. Relational contract was found to be positively related to affective, continuance and normative commitment but it was found to be not significant only in the case of normative commitment. Overall however, psychological contract was found to be negatively and significantly related with organizational commitment. This particular result however is probably due to the nature of both components of the (transactional and relational) psychological contract which are characteristically of polar opposites of each other. Nevertheless, this research has shown that that psychological contract could become a useful tool for fostering and promoting employees’ commitment to an organisation.